A Contextual Reading of Ethiopian Crosses through Form and Ritual - Gnisci, Jacopo (Aethiopica, 2020)
Maria Evangelatou’s book promises to explore new research questions and challenge Eurocentric approaches to Ethiopian crosses by presenting an analysis of their use and significance among the Christian orthodox population of Ethiopia. Unfortunately, the study fails to deliver on this promise due to a lack of direct engagement with Ethiopian voices and the relevant literature, and a reliance on publications that focus on noncontemporary or non-Ethiopian contexts. This lack of engagement with Christian Ethiopians leads to significant misinterpretations. Moreover, by adopting an approach to Ethiopian sources that fails to recognize the existence of significant shifts within the Ethiopian literary tradition, the author flattens Ethiopia’s historical dimension, and thus unintentionally reproduces the kind of Eurocentric representation of the country that she set out to challenge.